Idiopathic Normal-Pressure Hydrocephalus Revealed by Systemic Infection: Clinical Observations of Two Cases - Shinya Watanabe; Yasushi Shibata; Kosuke Baba; Yuhei Kuriyama; Eiichi Ishikawa (Neurology International)
Background/Objectives: Idiopathic normal-pressure hydrocephalus (iNPH) is a potentially reversible neurological disorder characterized by gait disturbance, cognitive impairment, and urinary incontinence. Its pathophysiology involves impaired cerebrospinal fluid (CSF) absorption, and recent research has highlighted the role of the glymphatic and meningeal lymphatic systems in this process. However, the factors that trigger the clinical manifestations of iNPH in subclinical cases remain poorly understood. Case Presentation: Herein, we report two rare cases of iNPH in which clinical symptoms only became apparent following systemic infections. An 82-year-old man presented with transient neurological deficits during a course of sepsis caused by Klebsiella pneumoniae. Neuroimaging revealed periventricular changes and mild ventricular enlargement. Shunting and a tap test led to significant improvements to both his gait and cognition. An 80-year-old man with a history of progressive gait disturbance and cognitive decline developed worsening urinary incontinence and acute cerebral infarction caused by Staphylococcus haemolyticus bacteremia. Magnetic resonance imaging revealed a ventriculomegaly with features of disproportionally enlarged subarachnoid space hydrocephalus and a corona radiata infarct. Clinical improvement was achieved after a ventriculoperitoneal shunt was placed. Conclusions: Our two present cases suggest that systemic inflammatory states may act as catalysts for the manifestation of iNPH in patients with predisposing cerebral ischemia or subclinical abnormalities in CSF flow, highlighting the need for higher clinical awareness of iNPH in older patients who present with neurological deterioration during systemic infections. Early diagnosis and timely shunting after appropriate infection control may facilitate significant functional recovery in such patients.